The New Normal: Social Media’s Novel Roles and Utilisation - Rety Palupi; Mincho Slavov (J-IKA : Jurnal Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas BSI Bandung, 2020)
In the last decade social media has seen a significant growth and influence that reached an unprecedent levels during the COVID-19 pandemic. This research aims to identify and validate the new roles and way social media can be utilised in the era of New Normal. In addition, the relationship between social media and the new normal will be explored in the light of the post COVID-19 protocols by applying uses and gratification theory. The authors argue that new normal is offering unique possibilities for development and expanding the social media features, functions and way of use. This research provides both academics and the business community with a comprehensive and up-to-date knowledge about the increasing influence of social media on people’s lifestyle.